Surface-modified composite fiber filter membrane as well as preparation method and application thereof
The surface-modified composite fiber filter membrane prepared by electrospinning technology, combined with the use of ZrO2 nanoparticles, solves the problem of degradation of insulation performance caused by moisture and impurities in aging mineral insulating oil, and achieves efficient purification of aging insulating oil and increases breakdown voltage.
Patent Information
- Application Number
- CN202411818815.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-11
AI Technical Summary
Due to the existence of moisture and impurities in aging mineral insulating oil, the insulation performance is degraded. The prior art is difficult to effectively remove these impurities, resulting in waste of resources and environmental pollution.
Electrospinning technology is used to prepare surface-modified composite fiber filter membranes, and ZrO2 nanoparticles are introduced into the filter membrane to improve the hydrophobic effect and specific surface area of the filter membrane, and to achieve accurate filtration of trace moisture and impurities in the aged mineral insulating oil.
Through this method, the breakdown voltage of aging insulating oil is significantly increased, resource waste and environmental pollution are reduced, and efficient purification of aging mineral insulating oil is achieved.
Smart Images

Figure CN119656891A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of insulating oil filtration treatment, and in particular to a surface-modified composite fiber filter membrane and a preparation method and application thereof. Background Art
[0002] Mineral insulating oil is an insulating material made of mineral oil as the base oil, with antibacterial agents, antifoaming agents, bactericides, etc. added. Compared with traditional insulating materials, it has the advantages of lower cost and thermal stability, and is widely used in the power industry, railway industry, petrochemical industry, etc. Among them, mineral insulating oil is the most commonly used in power transformers of all grades, and forms an oil-paper insulation system with insulating paper. Pure mineral oil has excellent insulation, arc extinguishing and cooling properties. In my country, many power transformers have been in operation for more than 20 years.
[0003] The oil-paper insulation system will continue to produce particulate impurities such as moisture, organic acid, metal and cellulose during the aging process. The moisture in the aged mineral oil is the number one killer that harms the insulation performance of the mineral insulating oil. The increase in moisture in the oil will significantly reduce the breakdown voltage of the insulating oil, thereby greatly deteriorating the insulation performance of the mineral insulating oil. The decline in the quality of mineral oil will directly lead to the decline in its insulation, arc extinguishing and cooling performance. Directly replacing the insulating oil is costly and will cause a certain degree of resource waste and environmental pollution. Therefore, the improvement of insulating oil purification technology is particularly important. Summary of the invention
[0004] The present invention provides a surface-modified composite fiber filter membrane and a preparation method and application thereof. ZrO2 nanoparticles are introduced into the filter membrane to improve the surface hydrophobic effect, thereby intercepting and adsorbing trace moisture and impurities in aged mineral insulating oil, thereby achieving the purpose of purifying the aged mineral insulating oil and effectively improving the breakdown voltage of the aged insulating oil.
[0005] In order to solve the above technical problems, one of the purposes of the present invention is to provide a method for preparing a surface-modified composite fiber filter membrane, comprising the following steps:
[0006] (1) PVA powder is added to a container containing a solvent and stirred evenly, ZrO2 nanoparticles are slowly added, and after stirring evenly, vacuum standing and degassing is performed to obtain a spinning solution;
[0007] The mass ratio of the PVA powder to the ZrO2 nanoparticles is (5-7):1, and the particle size of the ZrO2 nanoparticles is 20-40 nm;
[0008] (2) The spinning solution is added into an electrospinning machine, and the composite fiber filter membrane is prepared by using electrospinning technology.
[0009] By adopting the above scheme, the present application adopts electrospinning technology to prepare a filter membrane with a small fiber diameter, good uniformity, high porosity and large flux, and has a high efficiency in filtering micro impurities. Since the mineral insulating oil has good hydrophobicity, the present application introduces ZrO2 nanoparticles into the filter membrane, which can improve the surface effect of the filter membrane, increase the specific surface area and impurity adsorption effect, and can hydrophobically block trace moisture in the aged mineral insulating oil. At the same time, the particle size of the ZrO2 nanoparticles is not large, which can ensure that the pore size of the filter membrane is maintained small, and can adsorb and intercept micro impurities, thereby achieving precise filtration of moisture and impurities in the aged mineral insulating oil, achieving the purpose of purifying the aged insulating oil, and improving the breakdown voltage of the aged insulating oil.
[0010] As a preferred embodiment, in step (1), the PVA powder and ZrO2 nanoparticles are pre-dried at 60-80°C for 20-24h.
[0011] As a preferred embodiment, in step (1), the mass ratio of the PVA powder to the solvent is 1:(10-12).
[0012] As a preferred embodiment, the solvent is at least one of methyl phthalate, octyl phthalate and butyl phthalate.
[0013] As a preferred embodiment, in step (1), the stirring temperature is 35-45°C and the stirring rate is 350-400 r / min.
[0014] As a preferred embodiment, in step (1), the standing degassing time is 6-8 hours.
[0015] As a preferred embodiment, in step (2), the thickness of the composite fiber filter membrane is 1-1.5 μm.
[0016] As a preferred solution, in step (2), the temperature inside the electrospinning machine cabinet is controlled at 30-40°C, and the humidity is controlled at 30%-40%.
[0017] As a preferred embodiment, in step (2), the spinning solution is slowly sucked into the syringe of the electrospinning machine, and the bubbles in the syringe are fully removed. A stainless steel needle is used and connected to a positive high-voltage DC source. A flat-plate collector is connected to a negative high-voltage DC source. A conductive adhesive is used to stick tin foil to the flat-plate collector. The distance between the flat-plate collector and the syringe is controlled to be 15-17 cm. The pushing speed of the syringe is 0.7-0.8 mL / h to prepare the composite fiber filter membrane.
[0018] In order to solve the above technical problems, the second object of the present invention is to provide a surface-modified composite fiber filter membrane.
[0019] In order to solve the above technical problems, the third object of the present invention is to provide a surface-modified composite fiber filter membrane for use in the field of mineral insulating oil filtration and purification.
[0020] As a preferred solution, the method comprises the following steps: cutting the surface-modified composite fiber filter membrane and installing it on a sand core to perform vacuum filtration of the mineral insulating oil, with the vacuum degree being set to 0.02-0.05 MPa.
[0021] As a preferred solution, the mineral insulating oil is 25# Karamay mineral oil.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present application adopts electrospinning technology to prepare the filter membrane, which has the advantages of small fiber diameter, good uniformity, high porosity and large flux, and has high filtration efficiency for micro impurities. ZrO2 nanoparticles are introduced into the filter membrane to increase the specific surface area and provide impurity adsorption, and hydrophobic barrier is performed on trace moisture in aged mineral insulating oil, and micro impurities are adsorbed and intercepted, thereby achieving precise filtration of moisture and impurities in aged mineral insulating oil, effectively improving the breakdown voltage of aged insulating oil, and reducing the waste of mineral insulating oil resources and pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 : It is a graph showing the change of trace moisture and breakdown voltage of insulating oil after filtration by composite fiber filter membrane in the application examples of the present invention and the comparative application examples;
[0025] Figure 2 : is a water drop contact angle curve diagram of a surface-modified composite fiber filter membrane in the embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION
[0026] The technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. Unless otherwise specified, the raw materials used can be obtained commercially, and the same raw materials are used in parallel experiments.
[0027] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0028] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0029] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0030] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0031] Polyvinyl alcohol was obtained from Shanghai Aladdin Biochemical Technology Co., Ltd., model 1799;
[0032] Polytetrafluoroethylene comes from Daikin Industries, Ltd. of Japan, model DAIKIN PTFE L-5F.
[0033] Example 1
[0034] A surface-modified composite fiber filter membrane, the preparation method of which comprises the following steps:
[0035] (1) Polyvinyl alcohol (PVA) powder and ZrO2 nanoparticles were placed in a vacuum drying oven for 20 h in advance, the drying temperature was set to 60°C, and the dried PVA powder and methyl phthalate (DMP) solvent were weighed using a precision electronic balance at a mass ratio of PVA powder to solvent of 1:10, and the dried ZrO2 nanoparticles were weighed at a mass ratio of ZrO2 nanoparticles to PVA powder of 1:5, wherein the particle size of the ZrO2 nanoparticles was 20 nm;
[0036] (2) Pour methyl phthalate (DMP) solvent into a glass bottle and place it on a magnetic stirrer at a temperature of 35°C and a stirring speed of 350 r / min, so that PVA is slowly poured into the stirred solvent. During the stirring process, the glass bottle is sealed to reduce the volatilization of the solvent. ZrO2 nanoparticles are slowly poured into the solvent during the stirring process. After stirring until the mixed solution is clear and transparent, it is placed in a vacuum drying oven and allowed to stand for 6 hours for degassing;
[0037] (3) The temperature inside the WL-2C high-voltage electrospinning machine was controlled at 30°C and the humidity was controlled at 30%. The spinning solution was slowly sucked into a 10 mL syringe and the bubbles in the syringe were fully removed. A stainless steel needle was used and connected to a positive high-voltage DC source. The flat-plate collector was connected to a negative high-voltage DC source. A conductive adhesive was used to stick tin foil to the flat-plate collector. The distance between the flat-plate collector and the syringe was controlled to be 15 cm. The pushing speed of the syringe was 0.7 mL / h to prepare a 1 μm composite fiber filter membrane.
[0038] Example 2
[0039] A surface-modified composite fiber filter membrane, the preparation method of which comprises the following steps:
[0040] (1) Polyvinyl alcohol (PVA) powder and ZrO2 nanoparticles were placed in a vacuum drying oven for 22 h in advance, and the drying temperature was set to 70°C. The dried PVA powder and butyl phthalate (DBP) solvent were weighed using a precision electronic balance at a mass ratio of PVA powder to solvent of 1:11, and the dried ZrO2 nanoparticles were weighed at a mass ratio of ZrO2 nanoparticles to PVA powder of 1:6, wherein the particle size of the ZrO2 nanoparticles was 30 nm;
[0041] (2) Put butyl phthalate (DBP) solvent into a glass bottle and place it on a magnetic stirrer at a temperature of 40°C and a stirring speed of 380 r / min, so that PVA is slowly poured into the stirred solvent. During the stirring process, the glass bottle is sealed to reduce the volatilization of the solvent, and ZrO2 nanoparticles are slowly poured into the solvent during the stirring process. After stirring until the mixed solution is clear and transparent, it is placed in a vacuum drying oven and allowed to stand for 7 hours to degas;
[0042] (3) The temperature inside the WL-2C high-voltage electrospinning machine was controlled at 35°C and the humidity was controlled at 35%. The spinning solution was slowly sucked into a 10 mL syringe and the bubbles in the syringe were fully removed. A stainless steel needle was used and connected to a positive high-voltage DC source. The flat-plate collector was connected to a negative high-voltage DC source. A conductive adhesive was used to stick tin foil to the flat-plate collector. The distance between the flat-plate collector and the syringe was controlled to be 15 cm. The pushing speed of the syringe was 0.75 mL / h to prepare a 1 μm composite fiber filter membrane.
[0043] Example 3
[0044] A surface-modified composite fiber filter membrane, the preparation method of which comprises the following steps:
[0045] (1) Polyvinyl alcohol (PVA) powder and ZrO2 nanoparticles were placed in a vacuum drying oven for 24 h in advance, and the drying temperature was set to 80°C. The dried PVA powder and dioctyl phthalate (DOP) solvent were weighed using a precision electronic balance at a mass ratio of PVA powder to solvent of 1:12, and the dried ZrO2 nanoparticles were weighed at a mass ratio of ZrO2 nanoparticles to PVA powder of 1:7, wherein the particle size of the ZrO2 nanoparticles was 40 nm;
[0046] (2) Put octyl phthalate (DOP) solvent into a glass bottle and place it on a magnetic stirrer at a temperature of 45°C and a stirring speed of 400 r / min, so that PVA is slowly poured into the stirred solvent. During the stirring process, the glass bottle is sealed to reduce the volatilization of the solvent, and ZrO2 nanoparticles are slowly poured into the solvent during the stirring process. After stirring until the mixed solution is clear and transparent, it is placed in a vacuum drying oven and allowed to stand for degassing for 8 hours;
[0047] (3) The temperature inside the WL-2C high-voltage electrospinning machine was controlled at 40°C and the humidity was controlled at 40%. The spinning solution was slowly sucked into a 10 mL syringe and the bubbles in the syringe were fully removed. A stainless steel needle was used and connected to a positive high-voltage DC source. The flat-plate collector was connected to a negative high-voltage DC source. A conductive adhesive was used to stick tin foil to the flat-plate collector. The distance between the flat-plate collector and the syringe was controlled to be 15 cm. The pushing speed of the syringe was 0.8 mL / h to prepare a 1 μm composite fiber filter membrane.
[0048] Example 4
[0049] A surface-modified composite fiber filter membrane, wherein each step of the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), the mass ratio of ZrO2 nanoparticles to PVA powder is 1:7.
[0050] Example 5
[0051] A surface-modified composite fiber filter membrane, the preparation method of which has the same steps, reagents, equipment and process parameters as those in Example 1, except that in step (1), the particle size of the ZrO2 nanoparticles is 50 nm.
[0052] Comparative Example 1
[0053] A surface-modified composite fiber filter membrane, the preparation method of which comprises the following steps:
[0054] (1) Polyvinyl alcohol (PVA) powder was placed in a vacuum drying oven for 20 h in advance, the drying temperature was set to 60°C, and the dry PVA powder and methyl phthalate (DMP) solvent were weighed using a precision electronic balance at a mass ratio of PVA powder to dilution solvent of 1:10;
[0055] (2) Methyl phthalate (DMP) solvent was placed in a glass bottle and placed on a magnetic stirrer at a temperature of 35° C. and a stirring speed of 350 r / min, so that PVA was slowly poured into the stirred solvent. During the stirring process, the glass bottle was sealed to reduce the volatilization of the solvent. After stirring until the mixed solution was clear and transparent, it was placed in a vacuum drying oven and allowed to stand for 6 hours to degas;
[0056] (3) The temperature inside the electrospinning machine was controlled at 30°C and the humidity was controlled at 30%. The spinning solution was slowly sucked into a 10 mL syringe and the bubbles in the syringe were fully removed. A stainless steel needle was used and connected to a positive high-voltage DC source. The flat-plate collector was connected to a negative high-voltage DC source. A conductive adhesive was used to stick tin foil to the flat-plate collector. The distance between the flat-plate collector and the syringe was controlled to be 15 cm. The pushing speed of the syringe was 0.7 mL / h to prepare a 1 μm composite fiber filter membrane.
[0057] Comparative Example 2
[0058] A surface-modified composite fiber filter membrane, wherein each step of the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), ZrO2 nanoparticles are replaced by an equal amount of SiO2 nanoparticles, and the particle size of the SiO2 nanoparticles is 20 nm.
[0059] Comparative Example 3
[0060] A surface-modified composite fiber filter membrane, wherein each step of the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), ZrO2 nanoparticles are replaced by an equal amount of TiO2 nanoparticles, and the particle size of the TiO2 nanoparticles is 20 nm.
[0061] Comparative Example 4
[0062] A surface-modified composite fiber filter membrane, wherein each step of the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), PVA powder is replaced by an equal amount of polytetrafluoroethylene (PTFE).
[0063] Comparative Example 5
[0064] A surface-modified composite fiber filter membrane, wherein each step of the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that the mass ratio of ZrO2 nanoparticles to PVA powder is 1:10.
[0065] Comparative Example 6
[0066] A surface-modified composite fiber filter membrane, the preparation method of which has the same steps, reagents, equipment and process parameters as those in Example 1, except that in step (1), the particle size of the ZrO2 nanoparticles used is 50 nm.
[0067] Application Examples 1-5 and Comparative Application Examples 1-6
[0068] Application of a surface-modified composite fiber filter membrane in the filtration and purification of mineral insulating oil comprises the following steps:
[0069] The surface-modified composite fiber filter membranes of Examples 1-6 and Comparative Examples 1-6 were cut into membrane samples with a diameter of 4 cm and installed on a sand core for vacuum filtration of aged mineral insulating oil. The aged mineral insulating oil was 25# Karamay. The vacuum degree of the circulating vacuum water pump connected to the filtration device was set to 0.02 MPa. The trace moisture and power frequency breakdown voltage of the filtered mineral oil samples were measured.
[0070] Comparative Application Example 7
[0071] Application of a surface-modified composite fiber filter membrane in the filtration and purification of mineral insulating oil comprises the following steps:
[0072] The surface-modified composite fiber filter membrane of Example 1 was cut into membrane samples with a diameter of 4 cm and installed on a sand core for vacuum filtration of aged FR3 vegetable insulating oil. The vacuum degree of the circulating vacuum water pump connected to the filtration device was set to 0.02 MPa, and the trace moisture and power frequency breakdown voltage of the FR3 vegetable insulating oil sample after filtration were measured.
[0073] Performance testing
[0074] 1. The treated insulating oils of the application examples and comparative application examples were tested for micro-water content according to GB / T 7600-2014 standard. The test results are shown in Table 1 below.
[0075] 2. The treated insulating oils of the application examples and comparative application examples were subjected to power frequency breakdown voltage tests according to GB / T 507-2002 standard. The test results are shown in Table 1 below.
[0076] 3. Water drop contact angle: Refer to GB / T 30693-2014 standard and use SDC-100 contact angle meter to measure the contact angle of the composite fiber filter membrane used in the corresponding use case and comparative application example. Drop water on the surface of the composite fiber filter membrane and measure the contact angle formed by the water drop on the surface of the composite fiber filter membrane.
[0077] Table 1 - Performance test results of insulating oil before and after treatment in the application examples of this application and the comparative application examples
[0078]
[0079]
[0080] As shown in Table 1, compared with Comparative Example 1, the present application introduces ZrO2 nanoparticles into the composite fiber filter membrane, which can modify the surface of the filter membrane to have a higher specific surface area, making the surface hydrophobic effect more significant, and can hydrophobically block the trace moisture generated in the aged mineral insulating oil, and adsorb and intercept other micro impurities, thereby purifying the aged mineral insulating oil, reducing the water content of the insulating oil, and increasing the breakdown voltage of the insulating oil.
[0081] As shown in Table 1, in Comparative Examples 2-3, SiO2 nanoparticles and TiO2 nanoparticles were introduced into the filter membrane for surface modification, respectively. However, the filtering and purification effect of the filter membrane on the aged mineral insulating oil was not as good as that of ZrO2 nanoparticles. The moisture content in the insulating oil was still high after filtration, and the breakdown voltage was relatively low.
[0082] As shown in Table 1, the filter membrane of Comparative Example 4 is made of polytetrafluoroethylene, and ZrO2 nanoparticles are introduced for surface modification. However, due to the insufficient compatibility and dispersibility of ZrO2 nanoparticles in the polytetrafluoroethylene system, the hydrophobic effect of the filter membrane surface is poor, the interception accuracy of trace moisture in the aged mineral insulating oil is low, and the porosity is large. The filter membrane has poor adsorption and interception accuracy for trace impurities in the aged mineral insulating oil, resulting in a low breakdown voltage of the insulating oil after filtration.
[0083] As shown in Table 1, the ZrO2 nanoparticles introduced into the filter membrane of Comparative Example 6 have a particle size of 50 nm, which is relatively large, resulting in larger pores in the filter membrane. Trace water molecules in the aged mineral insulating oil can easily pass through the pores, resulting in low efficiency in intercepting moisture and impurities, so that the breakdown voltage of the insulating oil is still low.
[0084] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a surface-modified composite fiber filter membrane, characterized in that: The following steps are involved: (1) PVA powder is added to a container containing a solvent and stirred evenly, ZrO2 nanoparticles are slowly added, and after stirring evenly, vacuum standing and degassing is performed to obtain a spinning solution; The mass ratio of the PVA powder to the ZrO2 nanoparticles is (5-7):1, and the particle size of the ZrO2 nanoparticles is 20-40 nm; (2) The spinning solution is added into an electrospinning machine, and the composite fiber filter membrane is prepared by using electrospinning technology.
2. The method for preparing a surface-modified composite fiber filter membrane according to claim 1, characterized in that: In step (1), the PVA powder and ZrO2 nanoparticles are dried at 60-80°C for 20-24h in advance.
3. The method for preparing a surface-modified composite fiber filter membrane according to claim 1, characterized in that: In step (1), the mass ratio of the PVA powder to the solvent is 1:(10-12).
4. The method for preparing a surface-modified composite fiber filter membrane according to claim 1, characterized in that: The solvent is at least one of methyl phthalate, octyl phthalate and butyl phthalate.
5. The method for preparing a surface-modified composite fiber filter membrane according to claim 1, characterized in that: In step (1), the stirring temperature is 35-45°C, the stirring rate is 350-400 r / min, and the standing degassing time is 6-8 h.
6. The method for preparing a surface-modified composite fiber filter membrane according to claim 1, characterized in that: In step (2), the thickness of the composite fiber filter membrane is 1-1.5 μm.
7. The method for preparing a surface-modified composite fiber filter membrane according to claim 1, characterized in that: In step (2), the temperature in the electrospinning machine box is controlled at 30-40°C, and the humidity is controlled at 30%-40%. The spinning solution is slowly sucked into the syringe, and the bubbles in the syringe are fully removed. A stainless steel needle is used and connected to a positive high-voltage DC source. A flat-plate collector is connected to a negative high-voltage DC source. A conductive adhesive is used to stick tin foil to the flat-plate collector. The distance between the flat-plate collector and the syringe is controlled to be 15-17 cm. The pushing speed of the syringe is 0.7-0.8 mL / h to prepare the composite fiber filter membrane.
8. A surface-modified composite fiber filter membrane prepared by the method for preparing a surface-modified composite fiber filter membrane according to any one of claims 1 to 7.
9. Use of the surface-modified composite fiber filter membrane according to claim 8 in the field of filtration and purification of mineral insulating oil.
10. Use of a surface-modified composite fiber filter membrane according to claim 9 in the field of filtration and purification of mineral insulating oil, characterized in that: The following steps are involved: The surface-modified composite fiber filter membrane is cut and installed on a sand core for vacuum filtration of mineral insulating oil, and the vacuum degree is set to 0.02-0.05 MPa.
Citation Information
Patent Citations
Method for preparing electro spinning mesoporous zircite fiber film
CN101362649A
Electrostatic spinning solution of polyvinylidene fluoride and preparation method of electrostatic spinning solution
CN104480560A
Controllable-morphology high-porosity porous ceramic membrane supporting body and preparation method thereof
CN104774015A
Preparation process of suction-filtration integrated synthetic filter membrane for jatropha curcas vegetable insulating oil
CN113769589A
Preparation method of zinc oxide nanofiber membrane
CN114045611A